2005
DOI: 10.2105/ajph.2004.054858
|View full text |Cite
|
Sign up to set email alerts
|

Parent or Caregiver, Staff, and Dentist Perspectives on Access to Dental Care Issues for Head Start Children in Ohio

Abstract: Many Ohio Head Start children do not receive dental care. Medicaid and patient age were primary dental office limitations that are partly offset by the role Head Start plays in ensuring dental care. Dentists, Head Start staff, and parents/caregivers have different perspectives on the problem of access to dental care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 5 publications
0
15
1
4
Order By: Relevance
“…A survey conducted in Pelotas (Brazil) showed that 79.3% of children from two to five years of age had never visited the dentist 14 . Despite the fact that the percentage of children in this study who had never had a dental visit is much lower than in other studies [11][12][13][14] , this group should be the focus of oral health teams, since it may have the highest level of disease. It would appear that insufficient knowledge on the part of parents and legal guardians as to the importance of early first dental visits and cultural factors related to the notion that children up to age one do not need to see a dentist contributes to this phenomenon.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…A survey conducted in Pelotas (Brazil) showed that 79.3% of children from two to five years of age had never visited the dentist 14 . Despite the fact that the percentage of children in this study who had never had a dental visit is much lower than in other studies [11][12][13][14] , this group should be the focus of oral health teams, since it may have the highest level of disease. It would appear that insufficient knowledge on the part of parents and legal guardians as to the importance of early first dental visits and cultural factors related to the notion that children up to age one do not need to see a dentist contributes to this phenomenon.…”
Section: Discussioncontrasting
confidence: 59%
“…According to the National Household Sample Survey of 2008, approximately 80% of children 0 to 4 years old have never had a dental visit 12 . According to Siegal et al 13 , only 21.1% of American children less than six years of age have ever gone to the dentist. A survey conducted in Pelotas (Brazil) showed that 79.3% of children from two to five years of age had never visited the dentist 14 .…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com a última PNAD, realizada em 2003, aproximadamente 80% de crianças menores de cinco anos nunca haviam realizado uma consulta odontoló-gica 9 , o que corrobora os resultados do presente estudo, segundo o qual apenas uma pequena parte dos pré-escolares do Município de Canela (13,3%) já havia consultado o cirurgião-dentista (Tabela 1). Essa porcentagem foi menor que a encontrada em outros estudos internacionais 11,12,13 . Em 2000, apenas 21,1% das crianças ame- Tabela 1 Freqüências simples e percentuais e intervalos de confi ança de 95% de crianças que utilizaram serviços odontológicos de acordo com a idade.…”
Section: Discussionunclassified
“…They represent two different approaches to addressing childhood caries-one aimed at preventing or reducing the incidence of the disease, the other aimed at treating the disease where it occurs. With limited resources available for primary dental care, access to these services remains a problem [5][6][7][8] and careful consideration must be given to the best way of using these resources in order to improve the oral health of children.…”
Section: Introductionmentioning
confidence: 99%